An H1 -Galerkin Mixed Finite Element Approximation of a Nonlocal Hyperbolic Equation - Chen, Fengxin; Zhou, Zhaojie (Mathematical Modelling and Analysis, 2017)
In this paper we investigate a semi-discrete H1 -Galerkin mixed finite element approximation of one kind of nolocal second order nonlinear hyperbolic equation, which is often used to describe vibration of an elastic string. A priori error estimates for the semi-discrete scheme are derived. A fully discrete scheme is constructed and one numerical example is given to verify the theoretical findings.